Newer therapeutic agents for retinal diseases. (2nd January 2022) - Markan, Ashish; Neupane, Swechya; Agrawal, Rupesh; Gupta, Vishali
ABSTRACT: Introduction: Last few decades in medical retina have encountered significant development in the field of pharmacotherapy. With better understanding of molecular mechanisms and disease pathophysiology, alternate pathways are being targeted in various clinical trials. Areas covered: In this review, a comprehensive list of newer therapeutic agents in various retinal conditions like diabetic macular edema (DME), age-related macular degeneration (ARMD), inherited retinal diseases (IRDs) and non-arteritic ischemic optic neuropathy (NAION) have been elucidated. The review highlights alternate pathways involved in pathogenesis of DME and ARMD, and gives a brief summary of several phase I and phase II trials targeting these pathways. The review also briefly highlights the advancements in the field of gene therapy, stem cell transplantation, neuro-protection and retinal implants in IRDs. Lastly, available treatment options for NAION have been discussed. Expert opinion: Evidence based medicine has allowed researches and vision scientists to explore newer drugs and target alternate disease pathways. Promising results with initial clinical trials will pave the pathway for larger studies and allow clinicians to overcome treatment burden presently associated with available treatment options.